2016
DOI: 10.15252/emmm.201606493
|View full text |Cite
|
Sign up to set email alerts
|

Activin promotes skin carcinogenesis by attraction and reprogramming of macrophages

Abstract: Activin has emerged as an important player in different types of cancer, but the underlying mechanisms are largely unknown. We show here that activin overexpression is an early event in murine and human skin tumorigenesis. This is functionally important, since activin promoted skin tumorigenesis in mice induced by the human papillomavirus 8 oncogenes. This was accompanied by depletion of epidermal γδ T cells and accumulation of regulatory T cells. Most importantly, activin increased the number of skin macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 81 publications
(127 reference statements)
5
31
1
Order By: Relevance
“…Dendritic epidermal T cells (DETC; CD3 hi TCRβ − ) were significantly less abundant in the presence of the activin transgene (Fig. F), which is consistent with the DETC depletion in Act mice during skin tumorigenesis . A reduction in DETCs also occurred following Treg depletion (Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Dendritic epidermal T cells (DETC; CD3 hi TCRβ − ) were significantly less abundant in the presence of the activin transgene (Fig. F), which is consistent with the DETC depletion in Act mice during skin tumorigenesis . A reduction in DETCs also occurred following Treg depletion (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Activin is as a potent accelerator of the wound healing response , but the underlying cellular mechanisms are still largely unknown. Consistent with the effect of activin on Treg numbers in skin tumors and on Treg differentiation in the periphery , the percentage of CCR6 + effector cells among the Tregs was increased in wounds of Act mice. Expression levels of several proinflammatory cytokines, in particular of IL‐6, were increased in 7‐day wounds of Act mice.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It has been shown that activin A plays important roles in the development and progression of solid tumors including breast carcinoma (1), ovarian carcinoma (2), and colorectal carcinoma (3). In addition, a recent study has revealed that activin overexpression is an early event in murine and human skin tumorigenesis via attracting tumor-associated macrophages (4). Tumorassociated macrophages are thought to have important roles in progression of not only skin solid tumors but also cutaneous T-cell lymphoma, based on the reports which describe that the depletion of tumor-associated macrophages delays tumor formation of cutaneous T-cell lymphoma cells in skin (5) and that cutaneous T-cell lymphoma patients with an increased number of tumor-associated macrophages had worse prognosis (6).…”
mentioning
confidence: 99%